STRATEGI PENGEMBANGAN KAWASAN EKOWISATA PANTAI FIRDAUS DI DESA KEMA DUA KECAMATAN KEMA KABUPATEN MINAHASA UTARA (Development Strategy for Eco Tourism Area of Firdaus Beaches in Kema Dua Village, Kema, North Minahasa Regency) - Joecelin Piri; Jenny Baroleh; Audrey Maweikere (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
This study aims to determine the internal factors (strengths and weaknesses) and external factors (opportunities and threats) and to formulate a strategy for developing the Firdaus Beach ecotourism area. This research was conducted from March to May 2019. The study used primary data obtained directly from the object of research, which included tourists, managers, and sellers through direct interviews with 22 respondents using questionnaires prepared as well as secondary data obtained from books, journals, and literature related to the this study. Data were analyzed using SWOT analysis, measured by using IFAS analysis (Internal Factor Analysis Strategy) and EFAS (External Factor Analysis Strategy). The results showed that ecotourismdevelopment on Firdaus Beach was in quadrant 1. The strategy used was an aggressive one which are to increase the attractiveness and to increase the use ofÂ  the strengths and opportunities in developing the Firdaus beach ecotourism area in Kema Dua Village.Keywords: Development Strategy, Firdaus Beach, Ecotourism , SWOT Analysis